The Contribution of Moral in Building the Purposes of Legal Rulings - Abdel Karim Muhammad Bennani (Studi Multidisipliner: Jurnal Kajian Keislaman, 2023)
The moral in Islam is the source of his spirit because it is merged in all its rulings, and at all its costs; From doctrine, worship, treatment, contracts, felony, punishment, politics, and economics. Each section of jurisprudence finds the person in charge of morals inherent and rooted in it. Because it is at the heart of the message of the Prophet, may God’s prayers and peace be upon him, for worship has purposes that are not disturbed by morals in their essence, and transactions are based on morals. The study aims to emphasize that ethics is an integral part of the system of legal rulings. Legal rulings are a matter of establishing a coherent moral structure that combines consideration and ending. As consideration is orders that included good morals, and the completion of a marriage that included ugly morals, and they are the purposes of which are frank. Including the one that is derived from understanding, contemplation, and consideration, and if we separate them from moral purposes. We find ourselves in front of a legislative building that is limited to achieving the goal this introverted is the way to know the truth of the Sharia, and to understand the essence of the Islamic religion and the achievement of its major intentions.